Determining the effect of added zirconium on the bond character in TiFe alloys using scanning Kelvin probe force microscopy - Han, Huijun; Kim, Han-Jin; Kim, Hayoung; Sohn, So-Dam; Shim, Jae-Hyeok; Suh, Jin-Yoo; Shin, Hyung-Joon (ELSEVIER, 2020)
Alloying elements are known to enhance the first hydrogenation of TiFe alloys, although the mechanism has not yet been fully understood. The effects of Zr on the bond character of a TiFe alloy was investigated using scanning Kelvin probe force microscopy. Adding Zr led to increased formation of the TiFe2 and Ti2Fe phases. As for TiFe2 phase, where the added Zr substituted Fe, the substitution caused the bond character of the phase to become more covalent and less ionic due to the lower electronegativity of Zr compared to Fe. Subsequently, the work functions increased as a function of Zr content.
Keywords: HYDROGEN-STORAGE; MECHANICAL ACTIVATION; FETI; ZR